Dipeptidyl-Peptidase 4 Inhibitor Sitagliptin Ameliorates Hepatic Insulin Resistance by Modulating Inflammation and Autophagy in ob/ob Mice. (19th July 2018) - Zheng, Wenbin; Zhou, Jing; Song, Shasha; Kong, Wen; Xia, Wenfang; Chen, Lulu; Zeng, Tianshu
Abstract : Obesity and type 2 diabetes are the most common metabolic diseases globally. They are associated with inflammation, oxidative stress, autophagy, and insulin resistance. Sitagliptin, a dipeptidyl-peptidase 4 inhibitor, has been reported to show multiple biological activities beyond the antidiabetic property. This study was aimed at investigating the effect of sitagliptin on hepatic steatosis, insulin resistance, inflammation, and autophagy and exploring the underlying molecular mechanism. In the current study, ob/ob mice, a mouse model of genetic obesity and diabetes, were administered via gavage with sitagliptin 50 mg/kg daily for 4 weeks. Changes in glycolipid metabolism, inflammatory responses, and autophagy in the liver were evaluated. Body weight gain, lipid metabolic disorder, and hepatic steatosis as well as systemic and hepatic insulin sensitivity in ob/ob mice were significantly attenuated after sitagliptin treatment. Furthermore, sitagliptin decreased inflammatory responses by regulating macrophage M1/M2 polarization and inhibiting the activities of NF- κ B and JNK. Moreover, sitagliptin increased the levels of phosphorylation of AMPK and decreased those of mTOR. This study indicates that sitagliptin significantly ameliorates the development of hepatic steatosis and insulin resistance in ob/ob mice by inhibiting inflammatory responses and activating autophagy via AMPK/mTOR signaling pathway.